Empirical investigation of a photovoltaic-thermal system with phase change materials and aluminum shavings porous media. (April 2021) - Vaziri Rad, Mohammad Amin; Kasaeian, Alibakhsh; Mousavi, Soroush; Rajaee, Fatemeh; Kouravand, Amir
Abstract: Since a high photovoltaic panel (PV) temperature impacts the electrical output power, especially in tropical countries, the use of some cooling methods such as fluid flows, phase change materials (PCMs), and porous media has been suggested as an attractive option. In this study, these methods are integrated experimentally; a novel low-cost porous medium is developed using aluminum shavings, considered as waste materials in some industries, to increase the thermal conductivity of the phase change material. Then, the combination of this porous medium with salt hydrate is added to the water-based photovoltaic-thermal (PV/T) system; the electrical, thermal, and exergy efficiencies of the units are measured in July and December. The results of this research show that the photovoltaic-thermal unit, integrated with phase change material and porous medium, would have a high cooling performance by reducing the average temperature of the photovoltaic panel. The 24 °C reduction would augment the electrical efficiency by 2.5%, compared to solo PV, in the warm month. Also, it is found that, by using a porous medium, the melting time of the phase change material decreases by about 19%–25%. This method yields a maximum of 4.34% exergy efficiency improvement, compared to the single photovoltaic unit. Highlights: The performance of a photovoltaic-thermal system is experimentally investigated. About 35% PV temperature drop is observed by using improved phase change material. The system shows more than 60% thermal efficiency and 2.5% power increment. Maximally about 4.3% enhancement in exergy efficiency is observed for this system. The developed porous medium drops the phase change material melting time by 25%.